1996
DOI: 10.1073/pnas.93.5.1792
|View full text |Cite
|
Sign up to set email alerts
|

Human stanniocalcin: a possible hormonal regulator of mineral metabolism.

Abstract: We have isolated a human cDNA clone encoding the mammalian homolog of stanniocalcin (STC), a calcium-and phosphate-regulating hormone that was first described in fishes where it functions in preventing hypercalcemia. STC has a unique amino acid sequence and, until now, has remained one of the few polypeptide hormones never described in higher vertebrates. Human STC (hSTC) was found to be 247 amino acids long and to share 73% amino acid sequence similarity with fish STC. Polyclonal antibodies to recombinant hST… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
117
1
1

Year Published

1997
1997
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 189 publications
(120 citation statements)
references
References 23 publications
1
117
1
1
Order By: Relevance
“…Stanniocalcin1, encoded by STC1 gene, is a glycoprotein hormone and it has a role in many physiological processes, including bone development, reproduction, wound healing, angiogenesis and modulation of inflammatory response (Ishibashi and Imai, 2002;Chang et al, 2003). The STC1 gene is expressed in a wide variety of tissues, including the kidney, prostate, thyroid, bone and ovary (Chang et al, 1995;Olsen et al, 1996;Varghese et al, 1998). Recently, STC1 overexpression has been found in hepatocellular, colorectal, breast and medullary thyroid carcinomas (Fujiwara et al, 2000;Okabe et al, 2001;Watanabe et al, 2002;McCudden et al, 2004).…”
Section: Atxn1 and Stc1 Are Targets Of Mir-101bmentioning
confidence: 99%
“…Stanniocalcin1, encoded by STC1 gene, is a glycoprotein hormone and it has a role in many physiological processes, including bone development, reproduction, wound healing, angiogenesis and modulation of inflammatory response (Ishibashi and Imai, 2002;Chang et al, 2003). The STC1 gene is expressed in a wide variety of tissues, including the kidney, prostate, thyroid, bone and ovary (Chang et al, 1995;Olsen et al, 1996;Varghese et al, 1998). Recently, STC1 overexpression has been found in hepatocellular, colorectal, breast and medullary thyroid carcinomas (Fujiwara et al, 2000;Okabe et al, 2001;Watanabe et al, 2002;McCudden et al, 2004).…”
Section: Atxn1 and Stc1 Are Targets Of Mir-101bmentioning
confidence: 99%
“…In fish, it functions as a classic hormone that is secreted from endocrine glands, the Corpuscles of Stannius, in response to hypercalcemia and inhibits uptake of calcium through the gills and gut (Wagner et al, 1988;Sundell et al, 1992). In mammals, STC1 is also a secreted glycoprotein (Jellinek et al, 2000), but although recombinant human STC1 was found to be capable of inhibiting the uptake of calcium through the gills of goldfish (Olsen et al, 1996), and of regulating the flux of calcium and phosphate across rat intestine (Madsen et al, 1998) and kidney (Wagner et al, 1997), there is no evidence that it has a physiologic role in regulating serum calcium in mammals. Instead, mammalian STC1 is expressed in a variety of tissues (Chang et al, 1995(Chang et al, , 1996Olsen et al, 1996) and is thought to have an autocrine or paracrine role, but the possibility of an intracellular role also is suggested by evidence that STC1 localizes to mitochondria (McCudden et al, 2002;Westberg et al, 2007a).…”
Section: Introductionmentioning
confidence: 99%
“…It is secreted from the endocrine gland, corpuscle of Stannius and acts on the target tissues to regulate whole-body Ca 2C and P i homeostasis (Wagner et al 1993, Lu et al 1994. The mammalian homologue of STC1 was identified almost 15 years ago; its function, however, is largely not known (Chang et al 1995, Olsen et al 1996. Different from piscine, mammalian STC1 is expressed in a wide variety of tissues, acting on its target cells via autocrine/paracrine pathways (Varghese et al 1998, De Niu et al 2000.…”
Section: Introductionmentioning
confidence: 99%